Ecological rationality intelligence in the world - Todd, Peter M.; Gigerenzer, Gerd. (Oxford : Oxford University Press, 2012)
The contributors explore rationality as a match between mind & environment. Intelligent behaviour comes about by exploiting reliable structure in the world & hence some of the intelligence is in the world itself.
Description based on online resource; title from PDF title page (viewed on Mar. 16, 2012).
Includes bibliographical references and index.
Keywords: Environmental psychology; Heuristic; Reason